Martin Heidegger: ontologia, existência e mundo - Fernandes, Leila Medeiros (2007)
The research seeks the explanation of the following concepts: ontology, existence and world in the heideggerian phenomenology, in opposition to the metaphysician sense of world, as it has been considered by the ontology so far. In that direction, it had been approached the theme of the existence following the conductive thread of the understanding strutucture of Dasei while this being is constituted as an access to the subject of being and its sense.